2018
DOI: 10.1155/2018/8076274
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasitic Infections among Patients of King Fahd Medical City in Riyadh Region, Saudi Arabia: A 5-Year Retrospective Study

Abstract: This study is a retrospective analysis of the recorded intestinal parasitic infections for in- and outpatients visiting King Fahd Medical City, Riyadh, Saudi Arabia, from 2013 to 2017. In this study, a total of 5987 in- and outpatient were examined for intestinal parasitic infection. 30 patients out of 5987 were infected with 6 species of intestinal parasites with prevalence rate 0.5%. These parasites were Entamoeba histolytica (P = 0.27%), Cryptosporidium sp. (P = 0.1%), Giardia lamblia (P = 0.07%), Trichuris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 25 publications
4
29
5
1
Order By: Relevance
“…Intestinal protozoa infections (B. hominis, E. histolytica, E. coli and intestinal flagellates were prevalent than soil-transmitted helminth infection (A. lumbricoides, S. stercoralis, hookworm and S. mansoni). This finding is in contrast with the findings of a study conducted in Nepal [16] and Saudi Arabia [17] which revealed soil-transmitted helminth as the most predominant intestinal parasite. The low prevalence of soil-transmitted helminth infection in this study could be due to the periodic deworming exercise initiated by the regional School Health and Education Programme (SHEP) of Ghana Education Service / Ministry of Education and the Neglected Tropical Disease Control Programme (NTDCP) of the Ghana Health Service [18].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Intestinal protozoa infections (B. hominis, E. histolytica, E. coli and intestinal flagellates were prevalent than soil-transmitted helminth infection (A. lumbricoides, S. stercoralis, hookworm and S. mansoni). This finding is in contrast with the findings of a study conducted in Nepal [16] and Saudi Arabia [17] which revealed soil-transmitted helminth as the most predominant intestinal parasite. The low prevalence of soil-transmitted helminth infection in this study could be due to the periodic deworming exercise initiated by the regional School Health and Education Programme (SHEP) of Ghana Education Service / Ministry of Education and the Neglected Tropical Disease Control Programme (NTDCP) of the Ghana Health Service [18].…”
Section: Discussioncontrasting
confidence: 99%
“…The predominant intestinal protozoa parasites were intestinal flagellates (90.0%), followed by E. histolytica (5.7%). This could be due to poor sanitation conditions, contamination of water and improper hygiene [17]. This finding is contrary to studies conducted in Rwanda [19] and Egypt [20] where E. histolytica was the most prevailing intestinal protozoa parasite.…”
Section: Discussionmentioning
confidence: 57%
“…Although Cryptosporidium has been frequently detected in faecal samples of local inhabitants in the GCC countries (SA [66,76,77], Kuwait [50], UAE [80], Qatar [46], and Oman [64]), they have little published data regarding the occurrence of Cryptosporidium in the Gulf water supply. However, six studies in SA, UAE, and Kuwait have investigated Cryptosporidium in selected water resources in the GCC (Table 3), with interesting outcomes.…”
Section: Cryptosporidium Contaminating Water Resources In the Gcc Coumentioning
confidence: 99%
“…These countries are known to be endemic with many infectious diseases, including parasitic diseases. Moreover, many risk factors have been reported to be associated with expatriate workers that predispose themselves to cryptosporidiosis [45,47,48,76].…”
Section: Expatriate Labourers In the Gcc Countriesmentioning
confidence: 99%
“…The improvement of sanitary conditions in industrialized countries and the effectiveness of parasite control measures reduce the incidence of only some parasites. Prevention and control of parasitic diseases through constant monitoring of the epidemiological situation of these diseases depends, to a large extent, on the effective teaching and training of medical personnel in the field of medical parasitology, awareness of the risks that parasitic organisms may cause, and more effective intervention of supervision and control of sanitary− epidemiological services [20,21].…”
Section: Introductionmentioning
confidence: 99%